Subtype-specific human endogenous retrovirus K102 envelope protein is a novel serum immunosuppressive biomarker of cancer - Gong, Qinyuan; Xu, Rongzhen (Frontiers in Immunology, 2025)
Immune dysfunction is one of the hallmarks of cancer and plays critical roles in immunotherapy resistance, but there is no serum biomarker that can be used to evaluate immune-dysfunction status of cancer patients. Here, we identified subtype-specific human endogenous retrovirus K102 envelope (HERV-K102-Env) with immunosuppressive activity in circulating blood as a novel serum immunosuppressive biomarker of cancer. We first generated monoclonal antibodies against K102-Env with high sensitivity and specificity, and we developed an ELISA assay to detect serum K102-Env. We then investigated whether K102-Env and K108-Env proteins are present in circulating blood of cancer patients. We found K108-Env proteins were present in serum of both patients with cancer and healthy individuals. In contrast, K102-Env markedly increased in patients with PDAC, hepatocellular carcinoma (HCC), and non-small cell lung cancer (NSCLC) compared with healthy controls. The positive rates of K102-Env were 34.00%, 39%, and 28.0% in PDAC, HCC, and NSCLC, respectively, whereas only 5.0% of healthy individuals had marginally increased K102-Env. In the sera of PDAC patients, K102-Env was 36.63-fold higher than that of healthy controls. K102-Env significantly upregulated PD-1/PD-L1 and c-Myc expression levels of T cells. Importantly, serum K102-Env levels correlated well with advanced cancers and tumor biomarkers CA19-9 and AFP. These findings indicate that circulating K102-Env protein is a novel serum biomarker for evaluating immunosuppressive status and disease stage of patients with cancer.